TEMPERATURE-SENSITIVE FLOCCULATION DURING GROWTH OF SACCHAROMYCES CEREVISIAE - Williams, John W.; Ernandes, Jose R. [UNESP]; Stewart, Graham G. (Springer, 1992)
Cell wall surface proteins were extracted from a temperature-sensitive flocculent strain of Saccharomyces cerevisiae. Electrophoretic analysis identified two protein bands (28 and 43 kDa) present when grown at 21 degrees C. These proteins were initially absent when the strain was grown at 37 degrees C but intensified after 6 days of growth concomitant with the onset of flocculation.